ChemInform Abstract: Synthesis of Unsymmetrical Imidazolium Salts by Direct Quaternization of N‐Substituted Imidazoles Using Arylboronic Acids. Issue 37 (16th September 2014) - Li, Shiqing; Yang, Fan; Lv, Taiyong; Lan, Jingbo; Gao, Ge; You, Jingsong
Abstract 24 examples